Using HBMO Algorithm to Optimal Sizing & Sitting of Distributed Generation in Power System - Noradin Ghadimi (Bulletin of Electrical Engineering and Informatics, 2014)
This paper analyzes of HBMO placement method efficiency in comparison with PSO and GA in order to sizing and sitting of distributed generation in distribution power system. These algorithms for optimization in this paper is tested on IEEE 33 bus reconfigured test system. The proposed objective function considers active power losses and the voltage profile in nominal load of system. In order to use of optimization algorithms, at first, placement problem is written as an optimization problem which includes the objective function and constraints, and then to achieve the most desirable results, Optimization methods is applied to solve the problem. High performance of the proposed algorithm in mention system is verified by simulations in MATLAB software and in order to illustrate of feasibility of proposed method will accomplish.